Effect on Student’s Critical Thinking in Physics Classroom Using Virtual Laboratory - Malhotra, Jipsy (International Journal of Psychosocial Rehabilitation, 2024)
A congenial environment in the classroom always has innovation in the form of creativity, which leads to the construction of content. Creativity is one of the vital goals of education. The right mix of creativity with curriculum will transform the way students acquire knowledge and apply it in life. In this research paper, the researcher has discussed the effect on students critical thinking in physics classrooms using a virtual laboratory. The researcher has done a quasi-experimental study to see the effect of virtual laboratories using a pre-test post-test design. The statistical technique used is paired sample t-test. Results showed improvement in the critical thinking level of students.